2018
DOI: 10.17810/2015.81
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Sports Activities for Obese Youth in Socialization Process

Abstract: The purpose of this study is to examine the contribution of sport to obese youth duringsocialization, considering the socio-cultural and economic characteristics of obese adolescents. In the study participated 118 obese children members of Ankara Metropolitan Municipality Family Life and Youth Centers who played sports or participated in sport activities in the 15-18 age range. As a data collection tool, the socialization scale consisting of 69 questions developed by Sahan (2007) was used. A computer-aided dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
0
0
3
Order By: Relevance
“…The finding of this study supports the assertion made by Rasulovna (2021), Nazirov (2020) and Kusan et al (2018) on the contribute sports in reducing poverty, and further opens another chapter to consider sports as an alternative poverty reduction strategy. The researchers acknowledge the limitations of the study due to the sample population but agree that the finding of the study would trigger further and similar studies in many parts of world especially, in Africa and other developing countries.…”
Section: Resultssupporting
confidence: 91%
“…The finding of this study supports the assertion made by Rasulovna (2021), Nazirov (2020) and Kusan et al (2018) on the contribute sports in reducing poverty, and further opens another chapter to consider sports as an alternative poverty reduction strategy. The researchers acknowledge the limitations of the study due to the sample population but agree that the finding of the study would trigger further and similar studies in many parts of world especially, in Africa and other developing countries.…”
Section: Resultssupporting
confidence: 91%
“…Moreover, no significant disparities were observed between the two groups for these tests (p>0.05). Past research involving 7-8-year-olds undergoing pedagogical games found consistent results in the sit-reach test comparisons (Bilgiç et al, 2016& Kusan et al, 2018. Study of Urlu (2014) 10-12-year-olds also reinforced these findings, indicating no notable class-based differences.…”
Section: Discussionmentioning
confidence: 59%
“…En este sentido la perspectiva de los escolares contrasta con un estudio publicado en 2018 y hecho por Kusan et al, concluyen la existencia de una relación significativa entre la participación de los jóvenes obesos, en actividades deportivas y su nivel de socialización, así como el nivel de socialización de los jóvenes que practican deporte es mayor. Diferentes investigaciones coinciden con los resultados de la presente investigación, que el deporte y actividad física, tienen un papel importante en la socialización, auto imagen corporal, autoconfianza, así como la auto estima de los jóvenes, impactando en la calidad de vida, puesto que es una actividad que permite al individuo participar dinámicamente en los diferentes entornos sociales (Akil, 2022;Baciu et al, 2015;Kusan et al, 2018;Young et al, 2020). En otro sentido la mayoría de los estudiantes encuestados en el presente estudio, están totalmente de acuerdo que la actividad física y el deporte tienen beneficios para mejorar la salud.…”
Section: Discusionesunclassified